2016
DOI: 10.1007/s11113-016-9409-x
|View full text |Cite
|
Sign up to set email alerts
|

Planning for the American Dream: The College-Savings Behavior of Asian and Latino Foreign-Born Parents in the United States

Abstract: Rapid growth in the population of children of immigrants has occurred during an era of soaring college costs in the United States. Despite well-established knowledge that immigrant parents hold high educational expectations for their children and that children of immigrants will make up a large share of the U.S. college-aged population, little is known about how immigrant families prepare financially for their children's postsecondary education. We use data from the Education Longitudinal Study of 2002 to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Much of the existing research, however, focuses on saving behavior before students have begun college. Studies have found variation by family race, with White and Asian American families saving more than Black and Hispanic families (Bandelj and Grigoryeva 2021; Charles, Roscigno, and Torres 2007; Dondero and Humphries 2016). We focus on Asian American and White families in this research, since the literature shows these groups are less likely than Black or Hispanic Americans to rely on loans and may have access to greater family savings.…”
Section: Explaining Asian American-white Differences In College Inves...mentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the existing research, however, focuses on saving behavior before students have begun college. Studies have found variation by family race, with White and Asian American families saving more than Black and Hispanic families (Bandelj and Grigoryeva 2021; Charles, Roscigno, and Torres 2007; Dondero and Humphries 2016). We focus on Asian American and White families in this research, since the literature shows these groups are less likely than Black or Hispanic Americans to rely on loans and may have access to greater family savings.…”
Section: Explaining Asian American-white Differences In College Inves...mentioning
confidence: 99%
“…For example, Asian American students have the highest rates of college completion among all racial groups (Shapiro et al 2017), with 74 percent of those who start at 4-year degree-granting institutions completing their degrees within 7 years compared to 64 percent for White students (U.S. Census Bureau 2016). Studies have explored Asian American families' saving behaviors for their children's postsecondary education as one potential mechanism of Asian American students' postsecondary success (Dondero and Humphries 2016;Ouyang, Hanna, and Kim 2019). This financial planning may influence Asian American students to enroll in college because they perceive they are able to afford it, and may enable their timely completion, as they may enroll in institutions with high graduation rates and/or feel they do not need to stop out or drop out for financial reasons (Elliott and Beverly 2011).We add to the research on Asian American and White families' contributions to their children's college education in three ways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the United States, parents/guardians begin saving for their children’s postsecondary education early (Dondero & Humphries, 2016; Hillman, Gast, & George-Jackson, 2015; Sherraden, Johnson, Elliott, Porterfield, & Rainford, 2007), prior to the adoption of any broad-based merit-aid policies. In theory, the adoption of broad merit-aid policies diminishes the need for fiscal resources to cover tuition and fee expenses.…”
Section: Conceptual Frameworkmentioning
confidence: 99%